PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAT (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 006 SUNGAIMAJO KECAMATAN KUBU BAUSSALAM KABUPATEN ROKAN HILIR - Hidayat, Mahmul; Daud, Daman Huri; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstraction : Background of research is process learn to teach class of V SD Negeri 006 Sungaimajo Kecamatan Babussalam Kabupaten Rokan Hilir subject of IPA which still predominated by teacher so that student become passively, so given by items is result and teacher learn which not yet with average value of dibwah KKM. This Research aim to to know there is or do not it him influence model study of type cooperative of TSTS either through and also individual of klasikal to result of class student learn. of V subject of IPA SD Negeri 006 Sungaimajo Kecamatan Babussalam Kabupaten Rokan Hilir. This assessment is given to 20 student. Data collected to passing observation use observation sheet for data model study of type cooperative of Two Stay Two Stray ( TSTS) passing UH 1 and UH II for data result of learning. Result learn student mount at first cycle compared to before conducting of action or before PTK, as for make-up of result learn student from 45,83 at elementary score mount at I silus with mean 60,00 at cycle of II mount to become 80,20 and also improve activity learn from percentage mean 68,74% at cycle of I become 90,62% at cycle of II, the increasing of result learn student from 65,62% at cycle of I become 87,49% at cycle of II, and the increasing of complete learn student from 62,50% [at] cycle of I become 91,66% at cycle of II. Thereby result of from this research that applying of model study of type co-operative of Two Stay Two Stray ( TSTS) can improve hsil learn IPA class student of V SD Country 006 Sungaimajo District Of Citadel of Baussalam Sub-Province of Rokan Downstream.Keyword : Two Stay Two Stray ( TSTS), Result Learn